STUDY ON THE EFFECT OF BARREL LENGTHON SOME INTERIOR BALLISTIC CHARACTERISTICS FOR THE PISTOL IN 7.62 mm CALIBER - Hưng (Journal of Military Science and Technology, 2021)
This paper focuses on establishing a mathematical model to study the effect of barrel length on the muzzle pressure, the muzzle velocity, and the time the bullet moves in the barrel. This model was applied to the calculation for 7.62 mm K54 pistols with three different barrel lengths of 116 mm (7.62 mm K54 pistol origin), 120 mm , and 127 mm (7.62 mm K14VN pistol). The biggest deviation between the calculated results of the model and the results of solving the system of differential equations of internal ballistic is 1.69% (for the muzzle pressure) and 0.25% (for the muzzle velocity); Besides, the muzzle velocity values were compared with the experimental results for the 7.62 mm K54 VN and 7.62 mm K14VN pistols. The comparison results showed the reliability of the mathematical model.